Improving the Productivity of Manufacturing Process Through the Analysis of Work Measurement Results : Case study - Wahlberg, Laura (My University, 2022)
It has been written that improvement is necessary for every organization since the perfor-mance level of different processes is likely to decrease over time unless it is actively meas-ured, evaluated, improved and maintained. Lack of doing so, will lead to loss of competitive-ness since the competitors are still likely to continue improving their processes. This case study has been conducted for a Finnish company manufacturing products to na-tional and international markets. The purpose of this case study is to first establish the most common hindrances in the manufacturing process, and secondly to find out how to improve the manufacturing process to increase productivity. This thesis used secondary data from a time study conducted in the case company during 2021, as well as literature review on work measurement, and different methods which aim at productivity improvements through continuous improvement (CI) methods on quality and/or process, including Lean and Six Sigma. The results of the secondary data have been modified due to the anonymity of the case company. The results of the time study proved what had been observed on the case company factory floor. There were established four main causes of delay in the manufacturing process. There-fore, the thesis answered the requirements given to it. The thesis gives basis for further study in the line or in linking operations, yet it also calls for further study in the field of work measurement.

On kirjoitettu, että kehitys on tarpeen jokaiselle organisaatiolle, koska eri prosessien suorituskykytaso mitä todennäköisimmin laskee ajan myötä, ellei sitä aktiivisesti mitata, arvioida, paranneta ja ylläpidetä. Mikäli eri prosessien suorituskykytasoa ei aktiivisesti ylläpidetä, se johtaa kilpailukyvyn heikkenemiseen, sillä kilpailijat suurella todennäköisyydellä edelleen parantavat prosessiaan. Tapaustutkimus on tehty suomalaiselle yritykselle, joka valmistaa tuotteita kansallisille ja kansainvälisille markkinoille. Tämän tapaustutkimuksen tarkoituksena on ensin määrittää valmistusprosessin yleisimmät esteet ja toiseksi selvittää, miten valmistusprosessia voidaan paran-taa tuottavuuden lisäämiseksi. Tässä tutkielmassa hyödynnettiin tapausyhtiössä vuoden 2021 aikana tehdyn aikatutkimuksen toissijaisia tietoja sekä työn mittausta koskevaa kirjallisuuskatsausta ja erilaisia menetelmiä, joilla pyritään tuottavuuden parantamiseen jatkuvalla laadun ja/tai prosessin kehittämismenetelmillä, kuten jatkuva parantaminen, Lean ja Six Sigma. Toissijaisen tutkimuksen tulokset ovat muokattu tapausyhtiön nimettömyyden vuoksi. Aikatutkimuksen tulokset vahvistivat, mitä tapausyhtiössä oli havaittu. Valmistusprosessin viivästymiseen oli neljä pääasiallista syytä. Siksi opinnäytetyö vastaa sille annettuihin vaatimuksiin. Opinnäytetyö antaa pohjan jatkotutkimukselle saman tutkimuksen jatkumona tai rinnakkaisten toimintojen parissa, lisäksi opinnäytetyö kutsuu uusia lisätutkimuksia työn mittaamisen alalla.
Keywords: productivity; lean manufacturing; work measurement; time study; work study; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management